Hubungan Insomnia terhadap Kejadian Hipertensipada Lansia di Panti Sosial Tresna Werdha X Jakarta Selatan - Desi Putri Utanti; Rima Berlian Putri; Maria Susila Sumartiningsih; Ricky Riyanto Iksan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study was to identify the relationship between insomnia and the incidence of hypertension in the elderly at the Tresna Werdha X Social Home in South Jakarta. This study used a quantitative method with a cross-sectional analytical design that aimed to determine the relationship between two variables. The study population was all elderly people living at the Tresna Werdha X Social Home in South Jakarta with a total of 288 people. Data were collected using the Insomnia Rating Scale (IRS) questionnaire that had been translated into Indonesian by the Jakarta Biological Psychiatry Study Group (KSBPJ-IRS). The results showed a significance value of p < 0.001 (α = 0.05), which means there is a significant relationship between insomnia and blood pressure. The Chi-Square test value of 35.596 with degrees of freedom (df) = 1 strengthens the existence of a very strong relationship between the two variables. Thus, this study concludes that there is a significant relationship between insomnia and the incidence of hypertension in the elderly at the Tresna Werdha X Social Home in South Jakarta. Keywords: Elderly, Hypertension, Insomnia.